2023
DOI: 10.1002/jsfa.12529
|View full text |Cite
|
Sign up to set email alerts
|

Identification and preparation of selenium‐containing peptides from selenium‐enriched Pleurotus eryngii and their protective effect on lead‐induced oxidative damage in NCTC1469 hepatocytes

Abstract: BACKGROUND Lead (Pb) is a highly toxic and persistent substance that easily accumulates in living organisms, eliciting cellular toxicity and oxidative stress. Some selenium‐containing proteins and peptides prepared from plant extracts are beneficial for protecting the body's health and resisting external disturbances. In the present study, selenium‐containing peptide species were prepared from selenium‐enriched Pleurotus eryngii protein hydrolysates and to evaluate the benefits of selenium‐containing peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These characteristics have aroused particular interest because of the anti-cancer, hepatoprotective, anti-lipidemia, immune system strengthening, and other a good concentration of major nutrients, such as protein, peptides, minerals, terpenoids, traces of various elements, fiber, and polysaccharides (P. eryngii polysaccharides-PEPs). These characteristics have aroused particular interest because of the anti-cancer, hepatoprotective, anti-lipidemia, immune system strengthening, and other activities shown in vitro and in animal models [6][7][8][9][10]. For this reason, P. eryngii is classified among functional foods [11][12][13] and used to create "healthy snacks" [14], namely, foods with high nutritional and biological value (rich in fiber and protein, low in salt, sugar, fat, and calories) [11].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics have aroused particular interest because of the anti-cancer, hepatoprotective, anti-lipidemia, immune system strengthening, and other a good concentration of major nutrients, such as protein, peptides, minerals, terpenoids, traces of various elements, fiber, and polysaccharides (P. eryngii polysaccharides-PEPs). These characteristics have aroused particular interest because of the anti-cancer, hepatoprotective, anti-lipidemia, immune system strengthening, and other activities shown in vitro and in animal models [6][7][8][9][10]. For this reason, P. eryngii is classified among functional foods [11][12][13] and used to create "healthy snacks" [14], namely, foods with high nutritional and biological value (rich in fiber and protein, low in salt, sugar, fat, and calories) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, food‐derived peptides have attracted immense attention due to their extensive sources and desirable multiple bioactivities 7,8 . Scientific evidence has suggested that food‐derived peptides are safer than synthetic drugs, and it is highly desirable to employ food‐derived peptides with antioxidant activity to attenuate the risk of occurrence and aggravation of chronic diseases 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Scientific evidence has suggested that foodderived peptides are safer than synthetic drugs, and it is highly desirable to employ food-derived peptides with antioxidant activity to attenuate the risk of occurrence and aggravation of chronic diseases. 9,10 Collagen is a favorable source of bioactive substances, which can release peptides with higher antioxidant activity after enzymatic hydrolysis. 11 Up to now, a series of antioxidant collagen peptides have been isolated and identified, which can exhibit different degrees of free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is found in a variety of selenoproteins, including glutathione peroxidases (GPx), which are antioxidant enzymes found in both animals and humans (Savitha et al, 2014). Protective effects of selenium against acute and chronic toxicity has been well established in the literature (Qiao et al, 2022;Yu et al, 2023). It has been reported that like other poultry species, quails are extremely vulnerable to lead poisoning, altering the weight of the body and its organs as well as the blood, serum biochemistry and immunity (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%